Experience : new foundations for the human sciences - Lash, Scott (Cambridge, UK : Polity, 2018)
c
'Scott Lash makes a radical plea for the centrality of experience in the social and human sciences. This original book by a leading social and cultural theorist will be of interest to scholars and students across the social sciences, from sociology and cultural studies to anthropology and politics'--
Machine generated contents note: Contents Introduction: Three Types of Experience Chapter One Have We Forgotten Experience? 1.1 In Praise of the A Posteriori 1.2 Substance 1.3 New Totalitarianisms and Technological Phenomenology: The Chapters Chapter Two Experience in Antiquity: Aristotle's A Posteriori Technics 2.1 Technics and Praxis: Aristotle 2.2 Against Theoretical Reason: Praxis, Technics, Contingency 2.3 Form and Substance: Ancients, Christians and Moderns Chapter Three Subjective Experience: William James's Radical Empiricism 3.1 James's Radical Empiricism 3.1.1 James and Hume: Radical Empiricism and Classical Empiricism 3.1.2 Experience and its Functions 3.2 Pragmatism: Activities 3.3 Dewey or Formal Pragmatics 3.4 Some Conclusions Chapter Four Objective Experience: Methodenstreit and Homo Economicus 4.1 Methodenstreit: Formalists and Substantivists 4.1.1 Historical School: Subjective Experience and Institutions 4.1.2 Max Weber: Subjective Experience as Method, Objective Experience as Outcome 4.2 Classicals and Neoclassicals 4.2.1 Physics and Economics: From Conservation of Substance to Field of Utilities 4.2.2 Scottish Enlightenment 4.3 Conclusions: The Economic and the Political Chapter Five Hannah Arendt's A Posteriori Politics: Free Will, Judgment, and Constitutional Fragility 5.1 Ancients and Moderns 5.2 Pax Romana 5.3 After the Polis: Augustine and Free Will 5.4 Politics as Aesthetic Judgment 5.5 Conclusions: From Politics to the Technological System Chapter Six Forms of Life: Technological Phenomenology 6.1 Forms of Life: Transformations of Performative Language 6.1.1 Forms of Life and Exclusion: Homo sacer's experience 6.1.2 Language and Forms of life 6.2 Technological Forms of Life 6.2.1 Communicational Forms of Life 6.2.2 Entropy against Negentropy 6.2.3 Incompleteness: From Predications (Science) to Algorithms (Engineering) 6.2.4 System Encounter: War Games or Sex Games? 6.3 Conclusions Chapter Seven Aesthetic Multiplicity: The View and the Ten Thousand Things 7.1 Fuzzy Singularities 7.1.1 Views 7.1.2 Art and Singularities 7.2 The Gaze as Multiplicity 7.2.1 Beauty: China against Metaphysics 7.2.2 Mountains that Breathe (and Perceive) Chapter Eight Conclusions 8.1 Technology 8.2 Institutions 8.3 Metaphysics or Empirical Multiplicity.
Includes bibliographical references and index.
Keywords: Experience; Social sciences